2012
DOI: 10.1111/j.1349-7006.2012.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of p62/SQSTM1 is associated with poor prognosis in patients with lung adenocarcinoma

Abstract: p62/SQSTM1 is a selective substrate of autophagy, and aberrant accumulation of p62 has been observed in various pathological conditions. To understand the roles p62 plays in non-small-cell lung cancer (NSCLC), we carried out immunohistochemical analyses of p62 expression in a cohort of patients with annotated clinicopathological data. As analyses of murine and human hepatocellular carcinomas suggested a correlation between p62 and Nrf2 accumulations, we also examined NRF2 expression in the same cohort. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
139
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 46 publications
(101 reference statements)
11
139
0
1
Order By: Relevance
“…In cancer cells, the expression of autophagy related proteins is lower than that in normal cells, if cells fail to execute autophagy, the tumor progresses [16,17]. Previous studies identified that insufficient activation of autophagy-related signaling pathway in cancer cells results in insufficient autophagy, which further induces malignant phenotype [18,19]. Based on the data revealed in Fig.3, the signaling pathway of peiminine-induced elevation in autophagic flux involves repressing phosphorylation of mTOR through inhibiting upstream of PI3K/Akt and AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, the expression of autophagy related proteins is lower than that in normal cells, if cells fail to execute autophagy, the tumor progresses [16,17]. Previous studies identified that insufficient activation of autophagy-related signaling pathway in cancer cells results in insufficient autophagy, which further induces malignant phenotype [18,19]. Based on the data revealed in Fig.3, the signaling pathway of peiminine-induced elevation in autophagic flux involves repressing phosphorylation of mTOR through inhibiting upstream of PI3K/Akt and AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…Human lung carcinoma tissue was used as a positive control for NRF2, p62, and NQO1 immunostaining (Inoue et al 2012). As a negative control, normal rabbit, mouse, or goat IgG was used instead of the primary antibody in this study.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Moreover, recent data also indicate that p62/SQSTM1 plays an important role in the accumulation of NRF2 in carcinoma cells (Komatsu et al 2010, Inami et al 2011). An association between NRF2 accumulation and adverse clinical outcome of patients has been reported in lung (Solis et al 2010, Inoue et al 2012, gallbladder (Wang et al 2010), and ovarian (Konstantinopoulos et al 2011) carcinomas. These findings indicate that NRF2 is possibly involved in the growth and/or progression of these carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 protects cancer cells against stress from the microenvironment or anticancer drugs and confers radiation resistance on cancer cells (20)(21)(22). Indeed, patients with somatic mutations in NRF2 or KEAP1 have a poor prognosis (19,(22)(23)(24)(25).…”
mentioning
confidence: 99%